Factores socioeconómicos y su relación con la educación financiera en la población de la parroquia Palanda, cantón Palanda. - Alberca Manchay, Jandry Alexander (2024)
Financial education empowers people through specific knowledge for efficient management of their finances, preparing them to face possible economic contingencies that may damage their financial stability, in an environment of constant economic, social, demographic, and political evolution. Within this context, the objective of the research is to develop a financial education program for the inhabitants of the “Palanda” parish of the Palanda canton. For this purpose, a mixed approach was followed, leading to an exploratory, descriptive, experimental type study, which could be deduced through a survey of 352 people under the criteria of the Economically Active Population (EAP), taking into account the elderly, i.e., between the ages of 18 and 65 years, to collect information on variables and factors related to the level of financial education. Next, through an ordinal Logit model, the incidence of the factors affecting the main study variable was established. The results5 showed that most of the inhabitants of the Palanda parish are in level four and level three of financial knowledge, so a financial education program was developed and implemented, which allowed the participants to improve their financial knowledge. In conclusion, the financial education program had a significant influence in improving the financial knowledge of the inhabitants of the Palanda parish, allowing them to reach a level five of indispensable knowledge to manage money effectively.